Transformational Leadership, Organizational Communication, and Work Motivation as Determinants of Teacher Performance - Novalia Ariska; Yunus Handoko; Ike Kusdyah Rachmawati (Journal of Educational Management Research, 2026)
This study aims to examine the partial and simultaneous effects of transformational leadership, communication, and work motivation on teacher performance in primary education. A quantitative research approach using a survey design was applied, involving all 33 teachers as respondents. Data were analyzed using SPSS through validity and reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing with t-tests and F-tests. The findings show that transformational leadership has a positive and significant effect on teacher performance, highlighting the importance of effective leadership practices in supporting instructional quality and professional outcomes. In contrast, communication and work motivation do not demonstrate significant partial effects on teacher performance when examined independently. However, when tested simultaneously, transformational leadership, communication, and work motivation collectively exert a significant influence on teacher performance. These results suggest that transformational leadership is the most dominant factor in enhancing teacher performance. Therefore, school management should prioritize leadership development while strengthening communication systems and motivational strategies for performance improvement.